2000
DOI: 10.4049/jimmunol.165.7.3763
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody Against the 66-kDa Protein Expressed in Mouse Spleen and Thymus Inhibits Ly-6A.2-Dependent Cell-Cell Adhesion

Abstract: The Ly-6 locus encodes several cell surface proteins of 10–12 kDa. Some members of this multigene family may function in cell signaling and/or cell adhesion processes. T lymphocytes overexpressing Ly-6A.2 (one member of the Ly-6 gene family) protein homotypically aggregate when cultured in vitro. Further analysis of this homotypic aggregation suggests that Ly-6A.2 participates in cell-cell adhesion. These observations indicated the presence of a Ly-6 ligand(s) on the surface of lymphoid cells. In this study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Our previous reports suggest the presence of Ly-6A.2 ligand on the majority of B cells and macrophages (34,44). APC-dependent inhibition of CD4 ϩ Tg T cell responses to peptide Ag is consistent with these published data, because splenic APC is comprised of B cells and macrophages.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Our previous reports suggest the presence of Ly-6A.2 ligand on the majority of B cells and macrophages (34,44). APC-dependent inhibition of CD4 ϩ Tg T cell responses to peptide Ag is consistent with these published data, because splenic APC is comprised of B cells and macrophages.…”
Section: Discussionsupporting
confidence: 79%
“…Although the ligands that might bind Ly-6 proteins have been proposed (44,45), the functional consequence of their interaction with Ly-6 proteins remains unclear. We demonstrate that Ly-6A.2 expression negatively regulates Ag-specific CD4 ϩ T cell responses by interacting with a candidate ligand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ly-6A is expressed on pluripotent hematopoietic stem cells, developing thymocytes, and mature T cells (Spangrude et al, 1988;van de Rijn et al, 1989). Several studies have suggested a role for Ly-6A in T cell signaling and cell adhesion (English et al, 2000). A functional role for Ly-6A in myoblast differentiation, however, is unprecedented.…”
Section: Genes Expressed Only During Early Myoblast Differentiation Cmentioning
confidence: 99%